Negosiasi Identitas Budaya: Resistensi dan Hibriditas Mahasiswa di Tengah Dominasi Budaya Populer Global - Nurcholis Sunuyeko; Ike Dian Puspita Sari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2025)
This research analyzes cultural identity negotiation strategies among university students in Indonesia amidst the dominance of global popular culture, specifically the influence of Hallyu and Westernization. Employing a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews and digital observations of 12 students in urban environments. The results indicate that students do not passively adopt foreign cultures; instead, they undergo a "glocalization" process through selective hybridity. The findings identify three main typologies: adaptive hybridity, symbolic resistance through digital indigeneity, and aesthetic assimilation. While global elements are utilized as social capital for a modern self-image, local religious and moral values remain fundamental filters in the adoption process. However, the study also reveals significant risks of cultural alienation in the form of authenticity crises and cultural inferiority due to dominant transnational aesthetic standards on social media. This study concludes that contemporary student identity manifests as a dynamic "cultural mosaic." It suggests a repositioning of character education to foster critical cultural negotiation skills, enabling the younger generation to become global actors without losing their national identity roots.